Research progress on cell cycle regulation-related molecules in the development of oral squamous cell carcinoma - HOU Zeyu; TANG Jinru; LI Longjiang (Kouqiang hemian waike zazhi)
Oral squamous cell carcinoma (OSCC) is the most common oral and maxillofacial cancer. In‐depth research on the regulatory mechanism of cell cycle regulation‐related molecules has revealed that these molecules play various roles in the incidence and progression of OSCC. This paper analyzes the recent research progress of cell cycle regulation‐related molecules in OSCC, as well as the functional characteristics of related molecules in the development of OSCC, to find potential biomarkers for the early diagnosis and targeted therapy of OSCC, and to improve patient survival rate.